If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5(a + 4) + -1(4a + 4) = 4(5a + -2) + 5 Reorder the terms: 5(4 + a) + -1(4a + 4) = 4(5a + -2) + 5 (4 * 5 + a * 5) + -1(4a + 4) = 4(5a + -2) + 5 (20 + 5a) + -1(4a + 4) = 4(5a + -2) + 5 Reorder the terms: 20 + 5a + -1(4 + 4a) = 4(5a + -2) + 5 20 + 5a + (4 * -1 + 4a * -1) = 4(5a + -2) + 5 20 + 5a + (-4 + -4a) = 4(5a + -2) + 5 Reorder the terms: 20 + -4 + 5a + -4a = 4(5a + -2) + 5 Combine like terms: 20 + -4 = 16 16 + 5a + -4a = 4(5a + -2) + 5 Combine like terms: 5a + -4a = 1a 16 + 1a = 4(5a + -2) + 5 Reorder the terms: 16 + 1a = 4(-2 + 5a) + 5 16 + 1a = (-2 * 4 + 5a * 4) + 5 16 + 1a = (-8 + 20a) + 5 Reorder the terms: 16 + 1a = -8 + 5 + 20a Combine like terms: -8 + 5 = -3 16 + 1a = -3 + 20a Solving 16 + 1a = -3 + 20a Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add '-20a' to each side of the equation. 16 + 1a + -20a = -3 + 20a + -20a Combine like terms: 1a + -20a = -19a 16 + -19a = -3 + 20a + -20a Combine like terms: 20a + -20a = 0 16 + -19a = -3 + 0 16 + -19a = -3 Add '-16' to each side of the equation. 16 + -16 + -19a = -3 + -16 Combine like terms: 16 + -16 = 0 0 + -19a = -3 + -16 -19a = -3 + -16 Combine like terms: -3 + -16 = -19 -19a = -19 Divide each side by '-19'. a = 1 Simplifying a = 1
| 900=x-.5 | | 7(2y+7)+(-36y)= | | 6x^5-4x^2+10x=0 | | -6n-1n=16 | | x^8-2x=0 | | 8(-16)/2(-8)-5(-3) | | 4-4(2a-3)=0 | | 6-3|-8r-9|=-15 | | (2x-1)/(9-x^2) | | -3|9m+2|+10=10 | | y^1/6(y^11/6+y^23/6) | | log(x+1)+2*log(x)=log(x^2+8) | | 4-9|-6-b|=-14 | | 10-10|-8k+4|=40 | | 17/x+7 | | 7.6=p-6 | | -8|3-8k|=40 | | Ln(3x)+5=7 | | 2/7x14/3 | | 3|x/9|+7=8 | | 5(3x-2)-8(2x+3)-9=51 | | -2(2x+2)=4(2-x)-12 | | 2x^2+3=y | | 61-4x=10+19 | | m/-4=-2.27 | | -5(4a-5)=2(3-10a)+19 | | -52-5x=8-8x | | 31x-13=42 | | 2(3x+1)+5(3x+1)= | | 9[v+2]-3v=2(3v+3)-11 | | m/-0.4=-2 | | 1/5w+2=6/5w |